Creating Markets in Burkina Faso : Growing Burkina Faso’s Private Sector and Harnessing it to Bolster Economic Resilience - World Bank; International Finance Corporation (International Finance Corporation, Washington, DC, 2019)
A small landlocked economy in the heart of West Africa’s French-speaking Sahel, Burkina Faso is characterized by its modest economic size, with a rapid population growth, with one of the highest per capita birth rates in the world. Burkina Faso needs to create 300,000 jobs annually to match its demographic growth, while about ninety percent of its workers are in the informal sector. Despite sustained robust economic growth over the past two decades driven by cotton and gold exports, private investment is low. Compounding the considerable development challenges that it faces, Burkina Faso is currently confronted by acute security and climatic threats, together with emerging fiscal risks. This country private sector diagnostic (CPSD) therefore investigates whether opportunities exist for the private sector to contribute more substantially to Burkina Faso’s development. The CPSD proposes a platform for action aimed at boosting Burkina Faso’s development through greater private sector investment. The remainder of the report provides an overview of: (i) the private sector environment; (ii) the cross-cutting constraints to the private sector; (iii) the critical enabling sector bottlenecks to the private sector; (iv) the opportunities for the private sector; and (v) a series of priority private sector focused recommendations.